Optimizing the profit from a complex cascade of hydroelectric stations with recirculating water - Korobeinikov, Andrei (2011)
In modern reversible hydroelectric power stations it is possible to reverse the turbine and pump water up from a downstream reservoir to an upstream one. This allows the use of the same volume of water repeatedly and was speci cally developed for hydro-electric stations operating with in- su cient water supply. Pumping water upstream is usually done at times of low demand for electricity, to build up reserves in order to be able to produce energy during peak hours, thus balancing the load and making a pro t on the price di erence. In this paper, we consider a branched model for hydroelectric power stations interacting in a complex cascade arrangement. The goal of this study is to provide guidance in decision-making aimed at maximizing the pro t. A detailed analysis is made of a simpler reservoir con guration, which indicates that even though the problem is nonlinear, a bang-bang type of control is optimal, where the power stations are operated at maximum rates of flow. Some simple relationships between price and timing of decisions are calculated directly. A numerical algorithm is also developed.